Media use habits, negative encounters with the police, and perceptions of the police: the mainstreaming hypothesis versus the resonance hypothesis - Choi, Jaeyong (Criminal justice studies, 2021)
Media researchers have long considered the extent to which the media influence perceptions of the police. More recently, scholars have encouraged more specific investigations to determine if media effects can vary depending on the audience’s characteristics. The present article contributes to and extends this line of research by employing unique measures of the media considering various modes of media and content and by examining whether individual experiences condition media effects on perceptions of the police. Using a sample of college students from Southwestern Pennsylvania, results show that there are significant interaction effects between some media measures and audience characteristics, highlighting that it is critical to consider individual characteristics and experiences in understanding media effects on perceptions of the police. Our findings provide mixed support for both of the mainstreaming hypothesis and the resonance hypothesis.